Understanding drivers of private-sector compliance to large-scale food fortification: A case study on edible oil value chains in Bangladesh. (October 2021) - Ebata, Ayako; Thorpe, Jodie; Islam, Ainee; Sultana, Sabiha; Mbuya, Mduduzi N.N.
Highlights: Co-existence of non-fortified products disincentivizes producers to fortify. Limited product traceability disincentivizes producers to comply with the policy. Economic pressure prevents small-scale producers from adequately fortifying. Political tension leads to inconsistent law enforcement, and limited compliance. Enforcement should focus on the origin of bulk items by large-scale producers. Abstract: Micronutrient deficiency is a pertinent global challenge that affects billions of people and has deleterious health effects. Large-scale food fortification (LSFF) is a cost- effective way to tackle micronutrient deficiency and improve health outcomes, particularly in low- and middle-income countries (LMICs). However, the success of LSFF in LMICs is often hampered by limited compliance with fortification mandates by the private sector, who supply fortified foods. In this paper, we use a case study of the edible oil produced in Bangladesh to analyze the factors facilitating and impeding this compliance by for-profit actors. We identified four bottlenecks that disincentivize private sector actors' decision to comply. First, fortified and non-fortified products co-exist in the market, disincentivizing producers to invest in fortification. Second, the lack of traceability reduces the risk for large-scale producers' non-compliance with the regulation. Third, small-scale producers face economic pressures that prevent them from adequately fortifying oil products. Lastly, law enforcement is currently inconsistent, allowing the supply of under-fortified oil in the market. Given the evidence, we recommend to strengthen the control of bulk item fortification through more frequent and rigorous surveillance at the production level. This will ensure that resource constrained consumers who also have the greatest potential to benefit from added nutrients, remain able to access affordable and nutrient-enriched food.